Analisis Rasio Keuangan di PT. Bank Muamalat - Iyonu, Mentari Ariesta; yusuf, sri dewi (Program Studi Akuntansi, 2022)
To assess the financial condition and performance of a company, especially at Bank Muamalat Indonesia (BMI), the benchmark that is often used is a ratio or index that can connect two financial data. Analysis and interpretation of various ratios can provide a better view of the financial condition and performance of a company compared to financial data that is not in the form of ratios. Ratios that are usually used are liquidity ratios, profitability ratios and solvency ratios. The liquidity ratio shows BMI's ability to meet short-term obligations that must be met immediately by using current assets, or the company's ability to meet its financial obligations when billed. To measure the liquidity ratio, two ratios can be used, namely the current ratio and the quick ratio. The higher the earnings per share of the company, the higher the level of dividends distributed. The increase in the level of dividend payments will signal to investors that the company's profitability is getting better. Meanwhile, solvency is the company's ability to finance all financial debts, both long-term and short-term debt at the time of liquidation. The higher the ratio, the less company funds provided by shareholders, so it can be assumed that the company has a higher liquidity risk.